1993
DOI: 10.1002/macp.1993.021940229
|View full text |Cite
|
Sign up to set email alerts
|

Polylactones, 22 ABA triblock copolymers of L‐lactide and poly(ethylene glycol)

Abstract: Triblock copolymers were prepared from L-lactide and a poly(ethy1ene glycol) of a,, = 1020.With GeO, and SnO, only low conversions were obtained, regardless of the reaction temperature. Sb,O, caused partial racemization, and only SnO gave satisfactory results. When other samples of poly(ethy1ene glycol) were used (e. g., with Hn = 600 or 3 250), partial racemization occurred even with SnO. However, with Sn(I1) 2-ethylhexanoate, racemization-free triblock copolymers were obtained under the reaction conditions u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
93
0
1

Year Published

1997
1997
2003
2003

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 165 publications
(100 citation statements)
references
References 7 publications
6
93
0
1
Order By: Relevance
“…It was found that all CH 2 OH end groups of PEO are esterified with IBMD units using the trifluoroacetic anhydride (TFAA) method 21) . TFAA causes rapid esterification of OH end-groups, and the neighbouring CH 2 protons experience a downfield shift of about 0.6 0.1 ppm.…”
Section: Synthesis and Characterization Of Pibmd-b-peo-b-pibmdmentioning
confidence: 99%
“…It was found that all CH 2 OH end groups of PEO are esterified with IBMD units using the trifluoroacetic anhydride (TFAA) method 21) . TFAA causes rapid esterification of OH end-groups, and the neighbouring CH 2 protons experience a downfield shift of about 0.6 0.1 ppm.…”
Section: Synthesis and Characterization Of Pibmd-b-peo-b-pibmdmentioning
confidence: 99%
“…The syntheobtain poly ( 1-caprolactone ) -poly ( ethylene glysis of polyester-polyether type block copolymer col ) -poly ( 1-caprolactone ) triblock copolymer has attracted much attention. [1][2][3][4] Recently, it was ( PECL ) . reported that the synthesis of ABA type block copolymers comprising poly(L-lactide) (A) and poly-(ethylene glycol) (B) segments obtained via an-…”
Section: Introductionmentioning
confidence: 97%
“…Besides environmental conditions, such as temperature, the degradation rate is strongly dependent on the film thickness, 1 additives such as monomer, 2 basic compounds, 3 acid drugs 4 or superoxide ion, 5 and catalyst such as SnOct 2 or zinc metal, [6][7][8][9] etc. The molecular architecture, [10][11][12][13] hydrophilicity, [14][15][16] reasonable crosslink, 17,18 and surface modification 19,20 have vital influence on the degradation properties, too.…”
mentioning
confidence: 99%